A conceptual framework of holistic Muslim spiritual care in Shariah compliant hospital - Wan Mamat, Wan Hasliza; Hairulisa@Mohd Hairi, Nur Alia; Mohamad Shariff, Nurasikin; Machouche, Salah; Yusuf, Azlina (Academic Inspired Network, 2025)
Spiritual care plays a crucial role in patient well-being, addressing religious, spiritual, and existential concerns of holistic patient care. It involves respecting patients’ beliefs, values, and dignity through empathy, compassion, and guidance. Despite its importance, there is limited literature on frameworks for delivering spiritual care, especially from an Islamic perspective. This study aimed to revise and validate a holistic Muslim spiritual care framework in a Shariah compliant hospital setting. A qualitative study was conducted with participants in one hospital in Malaysia. Data were collected through focus group discussion in May 2023 to further refined and validated the framework. Thematic analysis was used to analyzed the data. The study identified four key stakeholders in the holistic spiritual care framework: patients, healthcare providers, hospital management, and family members. Four core elements, which are empathy, cooperation, trust, and responsibility were found to be essential for effective spiritual care delivery. This conceptual framework emphasizes the critical roles of each party in supporting the spiritual well-being of patients. Its implementation in hospital settings can guide the provision of holistic spiritual care in line with Islamic values. Further discussion is needed to explore the framework’s broader applicability and its integration into healthcare organizations